Armoured Fighting Vehicle Destruction System - Marcin SZCZEPANIAK (System niszczenia pojazdów pancernych i wozów opancerzonych, 2019)
The paper presents a system that is a worldwide-unique means designed for building engineering barriers, fitting into the quasi-intelligent battlefield concept. The weapons employed are an innovative solution that integrates acoustic, seismic, thermal and laser scanner sensors into a single quasi-intelligent decision-making system. The system enables deploying a minefield section which, after deactivating 1st and 2nd degree safeties, operate autonomously, selecting targets and eliminating them with an explosively formed projectile. The paper presents the concept of the system's design and results of tests of individual elements.
Keywords: Niszczenie pojazdów pancernych i wozów opancerzonych